Maintenance and Repair Work. Issue 2 (4th May 2019) - Vinck, Dominique
ABSTRACT: This essay review evaluates recent contributions in the field of maintenance and repair studies with a focus on a special issue of Tecnoscienza on this research field and a volume edited by Ignaz Strebel, Alain Bovet, and Philippe Sormani entitled Repair Work Ethnographies: Revisiting Breakdown, Relocating Materiality . These two publications provide important insights into empirical investigations of maintenance and repair work which raise stimulating questions for engineering studies, where these activities are often overlooked.